Transport channel engineering between MXene interlayers for Zn‐ion hybrid microsupercapacitor with enhanced energy output and cycle stability - Zhiqian Cao; Guangyao Hu; Weixing Feng; Jie Ru; Yujin Li (Carbon Neutralization, 2023)
Abstract Two‐dimensional (2D) transition metal carbonitrides/nitrides (MXene) materials have proven to be promising alternatives as novel capacitor‐type electrodes for aqueous Zn‐ion hybrid microsupercapacitors (ZHMSCs). However, during self‐assembly processes, serious restacking between 2D MXene nanosheets induced by strong van der Waals forces makes ion transport channels narrow within the compact MXene film electrodes, which would result in poor energy output of ZHMSCs. Herein, interlayer transport channel engineering is designed by intercalating bacterial cellulose (BC) between MXene interlayers to develop MXene/BC electrodes with fast ion transport channels in contrast to pure MXene electrodes. Benefiting from fast anion intercalation/deintercalation on MXene/BC capacitor‐type cathode and reversible Zn stripping/plating on Zn foil anode, the fabricated ZHMSCs exhibit wide working potential windows (1.36 V), high areal capacitance (404 mF cm−2), and landmark areal energy density (94 µWh cm−2 at 1 mA cm−2). The areal capacitance and energy density of the developed ZHMSCs are much higher than those of the ZHMSCs based on pure MXene capacitor‐type cathode (239 mF cm−2/57 µWh cm−2 at 1 mA cm−2). Besides, the developed ZHMSCs can perform more than 10,000 cycles, showing outstanding capacity retention. In general, our work provides a novel strategy to break through the performance bottlenecks afflicting MXene‐based ZHMSCs.